Pengembangan Modul Tenses Bahasa Inggris Siswa - Manik, Tri Fani; Sulistiyo, Urip Fani; Wulandari, Bunga Ayu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of the research on the development of the English language module is to produce learning products in the form of an English module that is in accordance with the needs and characteristics of class X students at SMK Muhammadiyah Jambi City. This research is a type of R&D (Research & Development) research using the ADDIE development model which consists of 5 stages, consisting of analysis (analysis), design (design), development (development), implementation (implementation) and evaluation (evaluation). The data collection in this study was observation and interviews which were used to conduct a needs analysis, while the questionnaire was used to obtain data on the feasibility of the product. The data analysis technique in this study used descriptive statistical analysis to analyze quantitative data obtained from expert validation questionnaires and product trial questionnaires. To analyze qualitative data using techniques to check the validity of the data, triangulation of sources, triangulation of methods and triangulation of theory. The results of the media expert validation were 48.75 with the